Spatial and temporal evolution characteristics of water resources in the Hanjiang River Basin of China over 50 years under a changing environment - Li, Yiting; Deng, Jinglin; Zang, Chuanfu; Kong, Ming; Zhao, Jieni (Frontiers in Environmental Science, 2022)
In the formulation of scientific water resource management systems and strategies for improving water resource utilization efficiency, the effects of land use change and climate change on the temporal and spatial distribution of water resources cannot be overlooked. And the Hanjiang basin is the main source of water supply to eastern Guangdong and southwestern Fujian, China. However, the basin is experiencing a significant imbalance between water resource supply and demand. This study investigated the spatiotemporal distribution of water resources in the Hanjiang River Basin under changing environmental conditions using the Soil and Water Assessment Tool model. The findings reveal that, from 1980 to 2020, changes in water resources significantly varied among sub-basins, reflecting spatial heterogeneity. Moreover, sub-basins with severe land use changes showed significant changes in water resources. From 1970 to 2020, the water resources of each sub-basin changed with climate change, indicating temporal variability. Under the combined effects of land use change and climate change, the amount of water resources decreased and its spatial distribution changed dramatically. At the same time, the evolution of water resources under climate change was consistent with that under the combined influence of both land use change and climate change, indicating that climate change is the primary driver. The findings provide theoretical guidance for water resource research and management.